Integrated Hedgehog signaling is induced following castration in human and murine prostate cancers1. Issue 2 (2nd July 2012) - Efstathiou, Eleni; Karlou, Maria; Wen, Sijin; Hoang, Anh; Pettaway, Curtis A.; Pisters, Louis L.; Maity, Sankar; Troncoso, Patricia; Logothetis, Christopher J.
Abstract BACKGROUND The interplay between androgen and Hedgehog (Hh) signaling pathways may be associated with prostate cancer progression and resistance to therapy. METHODS Tissue microarrays from prostatectomy specimens were derived from 53 patients treated preoperatively with androgen ablation (AA) with or without chemotherapy, and from 26 stage‐ and grade‐matched controls. A previously characterized androgen‐regulated human prostate cancer xenograft was used to conduct parallel murine studies. Expression of markers of interest was determined on both untreated and castrated tumors. RESULTS Four‐month exposure to AA or AA with chemotherapy led to a uniform increase in Hh signaling as compared to controls, paired with an inverse trend of androgen receptor (AR) and CYP17 expression in clinically derived specimens. Changes in the expression profiles of Hh signaling were observed in the epithelium and stroma, in response to genotoxic stress of androgen ablation and chemotherapy. A reduced expression of KI67 and increased bcl2 expression was observed in the malignant epithelial compartment. CONCLUSION To our knowledge, this is the first clinical evidence that Hh signaling is induced by AA or the combination of AA and chemotherapy and, by inference, contributes to castrate‐resistant progression of prostate cancer as supported by parallel human and murine studies. These data are in agreement with previous reports that implicate Hh signaling in castrate‐resistant progression of prostate cancer. Based on these findings, we are pursuing parallel clinical and murine investigations to determine if Hh signaling inhibition combined with AA will be more effective than AA alone. Prostate 73: 153–161, 2013. © 2012 Wiley Periodicals, Inc.